Analisis Faktor yang Mempengaruhi Peningkatan Nasabah di Bank BTN Syariah Kota Pasuruan dimasa Pandemi - Rachmad Nor Firman; Siti Ilfiah (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2021)
The current condition of the corona pandemic in indonesia has been running for almost a year, of course, people want to have this pandemic over quickly. However, when the situation has not improved as before and is still required to undergo new normal activities. This pandemic has changed our behavior in carrying out daily activities, including in terms of the world of work. Employed performance will greatly affect the progress of the company and its customers. Good performance will result in good business development of this company. On the contrary, poor performance will also have a bad impact on the company. Therefore, to support good performance it is necessary to increase the target customer. The purpose of this study is to analyze the effect on increasing BTN Syariah customers during the pandemic. The research method used uses quantitative descriptive. The results showed that the work environment has a positive influence on customers, especially customers will be a affaected by products in BTN Syariah Pasuruan City, one of which is he deposit savings product whose distribution for the results is higher. BTN Syariah continues to increase its target from month to month even to the point of having a target by increasing the realization of cunsumer financing 0 to 28,690 M as of December 31,2021.